The correlation between faith and self-esteem with shamans and supernatural power - Godlif Sianipar (Faculty of Social and Political Science, Universitas Airlangga, 2019)
This research aims to provide empirical data about the relation between faith and self-esteem with shamans and their supernatural power among the tribal-based religious community in North Sumatra. The main issue this research tackles is that in this modern society, there are those who still trust and use shamans and their supernatural power termed “Begu Ganjang”. Despite this, the development of the global economy can often cause difficulty, and as such, humans must possess the ability to survive and to overcome problems, in a term known as the “Adversity Quotient” (AQ). However, instead of using their AQ, some individuals with low self-esteem tend to place more faith in shamans and supernatural powers. This study uses a quantitative approach in the form of a questionnaire. By using either a Purposive or Judgmental Sampling method, from 600 people asked, there were answers from a total of 100 respondents (50 men and 50 women) from each of the following tribes in North Sumatra: Batak Toba, Mandailing, Pakpak, Simalungun, Karo, and Nias. The study applied SEM to analyze the relationship between endogenous variables of faith and self-esteem with the shaman and Begu Ganjang. The study found that the relation of faith to shamans = 0.19, and faith to Begu Ganjang = 0.00. This means that there is a small relation between faith and shaman, while there is no relation between faith and Begu Ganjang. Furthermore, the relation of self-esteem to shaman = - 0.13, and self-esteem to Begu Ganjang = - 0.06. The result of this study shows the following: 1) There is a correlation between the growth of the respondent’s faith and their trust in the shaman, and 2) The decrease of trust in shamans and Begu Ganjang will occur only if the respondent’s self-esteem increases. Finally, the results of this study may act as a point of reference for other studies that will examine the phenomenon of syncretism in Indonesia.